Initial hospitalisation for atrial fibrillation in Aboriginal and non-Aboriginal populations in Western Australia. Issue 9 (19th February 2015) - Katzenellenbogen, Judith M; Teng, Tiew Hwa Katherine; Lopez, Derrick; Hung, Joseph; Knuiman, Matthew W; Sanfilippo, Frank M; Hobbs, Michael S T; Thompson, Sandra C
Abstract : Objective: The epidemiology of atrial fibrillation (AF) among Aboriginal Australians is poorly described. We compared risk factors, incidence rates and mortality outcomes for first-ever hospitalised AF among Aboriginal and non-Aboriginal Western Australians 20–84 years. Methods: This retrospective cohort study used whole-of-state person-based linked hospital and deaths data. Incident hospital AF admissions (previous AF admission-free for 15 years) were identified and subsequent mortality determined. Disease-specific comorbidity histories were ascertained by 10-year look-back. Age-standardised incidence rates were estimated and the adjusted risk of 30-day and 1-year mortality calculated using regression methods. Results: Aboriginal patients accounted for 923 (2.5%) of 37 097 incident AF admissions during 2000–2009. Aboriginal patients were younger (mean age 54.8 vs 69.3 years), had lower proportions of primary field AF diagnoses and higher comorbidities than non-Aboriginal patients. The Aboriginal and non-Aboriginal age-standardised incidence rates per 100 000 for men 20–54 years were 197 and 55 (ratio=3.6), for women 20–54 years were 122 and 19 (ratio=6.4), for men 55–84 years were 1151 and 888 (ratio=1.3), and for women 55–84 years were 1050 and 571 (ratio=1.8). While 30-day mortality was similar, crude 1-year mortality risks in Aboriginal and non-Aboriginal patients were 20.6% and 16.3% (adjusted HR=1.24) and 14.4% and 9.9% in 30-day survivors (adjusted HR=1.58). Conclusions: The incidence (particularly at young ages) and long-term mortality following hospitalised AF is significantly higher in Aboriginal people. Better control of the antecedent risk factors for AF, improved detection and management of AF itself and prevention of its complications are needed.